2015
DOI: 10.1523/jneurosci.4509-14.2015
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Complex Wave Patterns in Primate Cerebral Cortex

Abstract: Slow brain rhythms are attributed to near-simultaneous (synchronous) changes in activity in neuron populations in the brain. Because they are slow and widespread, synchronous rhythms have not been considered crucial for information processing in the waking state. Here we adapted methods from turbulence physics to analyze ␦-band (1-4 Hz) rhythms in local field potential (LFP) activity, in multielectrode recordings from cerebral cortex in anesthetized marmoset monkeys. We found that synchrony contributes only a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
100
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(107 citation statements)
references
References 23 publications
7
100
0
Order By: Relevance
“…1), and previous analysis of plane wave propagation252833. Understanding the more complex spatiotemporal patterns (for example, spirals66) that appear during seizure requires the development and application of additional approaches67. Second, the computational model implements numerous simplifications.…”
Section: Discussionmentioning
confidence: 99%
“…1), and previous analysis of plane wave propagation252833. Understanding the more complex spatiotemporal patterns (for example, spirals66) that appear during seizure requires the development and application of additional approaches67. Second, the computational model implements numerous simplifications.…”
Section: Discussionmentioning
confidence: 99%
“…Waves are a canonical example of dynamical phenomena in biological systems [10]. A diversity of neuronal wave patterns have been observed on mesoscopic [11][12][13][14][15] and wholebrain scales [4,[16][17][18]. These waves are not merely epiphenomena: For example, they have been reproducibly observed in visual processing [19] -carrying the primary stimulus-evoked response in visual cortex [11,20]; reflecting information flow in response to dynamic natural scenes [21]; encoding directions of moving stimuli [22]; encoding stimulus positions and orientations [23]; underlying bistable perceptual rivalry [24]; reinforcing recent visual experience [25]; and also occur pathologically during visual hallucinations [26].…”
Section: Introductionmentioning
confidence: 99%
“…They have also been implicated in sensorimotor processing of saccades [29], propagating seizure fronts [30,31], and observed during sleep with a possible role in memory consolidation [4]. Waves have been reported in diverse neuroimaging modalities including voltage-sensitive dyes (VSD) [11,20,25,[32][33][34], local field potentials [12,15,21,22,29], electrocortigraphy [4], electroencephalography (EEG) [16,17], magnetoencephalography (MEG) [35], fMRI [24]; and inferred from close analysis of psychophysical phenomena [36]. The widespread occurrence of cortical waves opens many questions [18]: What is their basis?…”
Section: Introductionmentioning
confidence: 99%
“…As exemplified by recent studies involving population recordings in marmoset MT, many questions about the perceptual significance of neural activity can only be answered by looking at population responses. For example, spiking activity in MT is influenced by the complex wave patterns in the local field potential (Townsend et al, ). This study showed that dense, high‐channel count arrays allow for studying a myriad of wave patterns and create a foundation for understanding the way brain flexibly and dynamically coordinates neural activity.…”
Section: Future Directions and Conclusionmentioning
confidence: 99%